Chilling effects in the internet age: three case studies - Penney, JW (2015)
This thesis is an empirical legal investigation into regulatory chilling effects in online contexts. Internet censorship is on the rise globally and state surveillance and cyber-policing capabilities are rapidly evolving. Understanding regulatory "chilling effects"—the idea that laws, regulations, or state surveillance can deter people from exercising their freedoms or engaging in legal activities—has thus today taken on greater urgency and public importance. Yet, the notion is not uncontroversial; many commentators have questioned the existence and impact of regulatory chilling effects, particularly in online contexts. It does not help that previous studies on regulatory chilling effects are generally narrow in methodological and theoretical approach and concern traditional media contexts, shedding little light on how chilling effects may work online. Drawing on a theoretical framework that synthesizes traditional chilling effects theory—forged largely by legal theorists Frank Schauer and Daniel Solove—and informed by insights from both online privacy and computer mediated communications (CMC) research, this thesis addresses this gap in the literature with an innovative research design that explores regulatory chilling effects online, with case studies exploring its comparative, regulatory, and surveillance-related dimensions. In concrete terms, this thesis provides empirical and theoretical foundations not only for the notion of regulatory chilling effects online but also factors that influence them. The first case study, a first-of-its-kind online survey with over 1200 respondents, provides general empirical support for the existence of regulatory chilling effects in online contexts, including comparative insights, that is, how some forms of regulation or surveillance may have more significant regulatory chilling effects than others, and why. The second case study examines whether widely covered revelations in June 2013 concerning NSA/PRISM online surveillance has had a chilling effect on Wikipedia users. The third case study is an investigation of the United States Digital Millennium Copyright Act (DMCA)’s controversial notice and takedown copyright enforcement system, a scheme often criticized for creating chilling effects online. This DMCA study is carried with a sample of 500 Google Blogs and 500 Twitter accounts and offers insights into how regulatory chilling effects work in practice, along with insights and implications of automated or "robotized" legal enforcement and the DMCA's international impact. Ultimately, this thesis addresses substantial gaps in existing research and literature concerning the existence, scope, impact, and permanence of regulatory chilling effects, and factors that influence them, while helping lay the foundation for a theory of regulatory chilling effects for online contexts. It also has substantial methodological contributions, offering unique and innovative methods for measuring and exploring regulatory chilling effects that can be re-deployed or built upon in future research